2007
DOI: 10.1002/art.23157
|View full text |Cite
|
Sign up to set email alerts
|

Risks and relative risks of Wegener's granulomatosis among close relatives of patients with the disease

Abstract: Objective. The etiology of Wegener's granulomatosis (WG) supposedly involves interplay between genetic susceptibility and environmental triggers. However, little is known about whether WG actually clusters in families. Information on the degree of familial aggregation in WG is of clinical relevance, because patients with WG often want to know whether their diagnosis puts their closest relatives at increased risk of the disease. The aim of this study was to investigate the risk of WG in relatives of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 42 publications
2
43
1
1
Order By: Relevance
“…This marked disease heterogeneity may be influenced at least in part by genetic factors, which is in accord with GWAS data showing an association between AAV and genetic factors [10]. A genetic influence also has been suggested by familial occurrences [69] and a greater frequency in first-degree relatives [70]. A US cohort study showed that GPA was more prevalent in Caucasians than Blacks [71].…”
Section: Genetic Association In Aavsupporting
confidence: 58%
“…This marked disease heterogeneity may be influenced at least in part by genetic factors, which is in accord with GWAS data showing an association between AAV and genetic factors [10]. A genetic influence also has been suggested by familial occurrences [69] and a greater frequency in first-degree relatives [70]. A US cohort study showed that GPA was more prevalent in Caucasians than Blacks [71].…”
Section: Genetic Association In Aavsupporting
confidence: 58%
“…An increased familial incidence of GPA with a relative risk for first degree relatives of 1.56 indicates that genetic factors are of importance [7]. A number of genetic polymorphisms have been associated with vasculitis including MHC and α 1 -antitrypsin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Different variants within each gene may be associated with different polymorphisms, for example AAV is associated with rs41295061. Aberrant transcription of neutrophil genes, a consequent loss of epigenetic silencing of MPO and PR3 in small vessel vasculitis patients, can be a synergistic factor in this disease (11,(93)(94)(95)(96). Additionally, a number of polymorphisms have been identified in KD from medium-size vessel vasculitis and genetic susceptibility is important for the development of coronary artery aneurysms.…”
Section: Genetic Implications Of Vasculitismentioning
confidence: 99%
“…Continued use of the drug inducing vasculitis can lead to irreversible and life-threating vasculitic organ damage ( end-stage renal disease or pulmonary hemorrhage) (93,(102)(103)(104)(105). COX-2 inhibitors can also cause fatal allergic vasculitis.…”
Section: Drugs Can Be Another Cause Of Aavmentioning
confidence: 99%